Effects of Mild Cognitive Impairment on the Event-Related Brain Potential Components Elicited in Executive Control Tasks - Zurrón, Montserrat; Lindín, Mónica; Cespón, Jesús; Cid-Fernández, Susana; Galdo-Álvarez, Santiago; Ramos-Goicoa, Marta; Díaz, Fernando (Frontiers in Psychology, 2018)
We summarize here the findings of several studies in which we analysed the Event-Related Brain Potentials (ERPs) elicited in participants with mild cognitive impairment (MCI) and in healthy controls during performance of executive tasks. The objective of these studies was to investigate the neural functioning associated with executive processes in MCI. With this aim, we recorded the brain electrical activity generated in response to stimuli in three executive control tasks (Stroop, Simon and Go/NoGo) adapted for use with the ERP technique. We found that the latencies of the ERP components associated with the evaluation and categorization of the stimuli were longer in participants with amnestic MCI than in the paired controls, particularly those with multiple-domain amnestic MCI, and that the allocation of neural resources for attending to the stimuli was weaker in participants with amnestic MCI. The MCI participants also showed deficient functioning of the response selection and preparation processes demanded by each task.